Organizational capabilities: Dynamic in nature - Dávila, José Camilo (Pontificia Universidad Javeriana, 2013)
Drawing upon research findings of some authors, this paper is putting forwardsa novel definition of organizational capabilities pinpointing the nature, featuresand potential of this notion. This definition suggests an alternative to the difficultyto establish a typology of organizational capabilities. The two componentsmaking up such a definition are exemplified on the basis of a case analysis,i.e., the dialogic nature engrained in the governance capacity, and the dual dimensioncharacterizing the way how such organization capabilities are beingput into practice. Thus, such a definition provides for an explicit and coherentconceptual basis for further research endeavours to be undertaken vis-à-visorganizational capabilities.